Sounding the Cape: Music, Identity and Politics in South Africa. Denis-Constant Martin. 2013. Somerset West, South Africa: African Minds. 444pp. - Bekker, Simon (International Library of African Music, 2013)
pages: [183]-186
Keywords: South Africa; African Music